Gluten-free bakery products - Semenova, Anastasia; Prikhodko, Julia; Drobot, Vira (My University, 2016)
The abstracts deals with the types of gluten-related disorders and the necessity of creating gluten-free baked goods. An experience of modern manufacturing products for special purposes is considered. In order to improve consumer properties of products it is offered to use multicomponent mixture compositions.
Keywords: gluten-related disorders; gluten-free bread; transglutaminase; gluten-free flour; dry protein; глютензалежні захворювання; безглютеновий хліб; трансглутаміназа; безглютенове борошно; сухий білок; кафедра технології хлібопекарських і кондитерських виробів; глютензависимые заболевания; безглютеновый хлеб; трансглутаминаза; безглютеновая мука; сухой белок